Identification of Flavonoids and Activity Test of Red Betel Leaf Fractions (Piper crocatum Ruiz & Pav) on Reducing Blood Sugar Levels in Diabetic Mice - Putra, Moch Racheal Ocwanda; Sa'ad, Muhammad; Ovikariani, Ovikariani (Universitas Muhammadiyah Surakarta, 2026)
Diabetes mellitus (DM) is a metabolic disease that can be life-threatening. Treatment for type 2 DM can use oral hypoglycemic drugs, but sometimes they have significant side effects. Red betel leaf extract is an antidiabetic drug derived from nature. The extract still contains impurities that can interfere with its effectiveness. The aim of this study was to determine the presence of flavonoids and the effect of each red betel leaf fraction as a blood sugar lowering agent. The research method used was analytical experimentation using maceration extraction using 70% ethanol solvent and continued with liquid-liquid fractionation using water, ethyl acetate, and n-hexane solvents. Antidiabetic activity was measured using a glucometer and indicated by the % reduction in blood sugar levels in each group. The results of flavonoid identification showed that the extract, water fraction, and ethyl acetate fraction of red betel leaves contained flavonoid compounds, while the n-hexane fraction did not contain flavonoid compounds. The percentage of reduction in blood sugar levels in each group were negative control (9.19%), positive control (50.04%), extract (41.70%), water fraction (47.33%), ethyl acetate fraction (56.40%), and n-hexane fraction of red betel leaves (34.95%). Based on the results, it can be concluded that the research group of ethyl acetate fraction and water fraction of red betel leaves have the potential as antidiabetics because not significantly different from the positive control glibenclamide. The best percentage value of blood sugar reduction is the ethyl acetate fraction group of red betel leaves with an average of 56.40%.